2016
DOI: 10.1038/srep21677
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of adults Xp11.2 translocation renal cell carcinoma by immunohistochemistry and FISH assays: clinicopathological data from ethnic Chinese population

Abstract: This study aimed to assess the utility of transcription factor E3 (TFE3) break-apart fluorescence in situ hybridization (FISH) assay in diagnosis of Xp11.2 translocation renal cell carcinoma (Xp11.2 RCC) and to compare the clinicopathological features between adult Xp11.2 RCC and non-Xp11.2 RCC. 76 pathologically suspected Xp11.2 RCCs were recruited from our institution. Both TFE3 immunohistochemistry (IHC) and TFE3 FISH assay were performed for the entire cohort. The progression-free survival (PFS) and overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 31 publications
3
52
0
Order By: Relevance
“…Since being recognized as a distinct entity by the World Health Organization (WHO) in 2004 [1], Xp11.2 translocation renal cell carcinoma (Xp11.2 tRCC) has attracted broad attention [25]. The term of Xp11.2 tRCC derived from several different chromosomal translocations of Xp11.2 breakpoints and formatting of TFE3 fusion gene, which resulted in a significant overexpression of TFE3 protein in tumor cells.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since being recognized as a distinct entity by the World Health Organization (WHO) in 2004 [1], Xp11.2 translocation renal cell carcinoma (Xp11.2 tRCC) has attracted broad attention [25]. The term of Xp11.2 tRCC derived from several different chromosomal translocations of Xp11.2 breakpoints and formatting of TFE3 fusion gene, which resulted in a significant overexpression of TFE3 protein in tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although immunohistochemical staining for TFE3 (TFE3-IHC) serves as the basic method for the diagnosis of Xp11.2 tRCC, numerous reports have shown that TFE3-IHC has fairly high false-positive rates and low predictive values, which results in misdiagnoses in patients [4, 911]. To date, TFE3 break-apart fluorescence in situ hybridization (FISH) is regarded as the best method to diagnose Xp11.2 tRCC due to its advantages of high sensitivity and specificity [2, 12–15]. In the current study, 34 cases of Xp11.2 tRCC were diagnosed using a TFE3 break-apart FISH probe.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…False positive and negative rates for translocation RCC with this modality have been reported as 6.7% and 4.3%, respectively 5. Fluorescence in situ hybridisation assay may be more sensitive and specific4 but is less widely used.…”
Section: Discussionmentioning
confidence: 99%
“…However, no published algorithms exist for this uncommon neoplastic entity, with treatment being guided by contemporary management of clear cell RCC and literature reviews. As for other RCC subtypes, surgical resection remains the mainstay of treatment for non-metastatic translocation RCC 5. While radical nephrectomy is thought to offer greatest cancer-free survival rates, partial nephrectomy has been successfully performed in a series of four patients with 3 years’ follow-up 3.…”
Section: Discussionmentioning
confidence: 99%